The road to desistance: the relationship between formal institutions of social control, informal social bonds, and intermittency in offending - Humphrey, Tamara (Deviant behavior, 2024)
The current study examines the relationship between formal social control, informal social bonds, and intermittency in offending. Using data from a Canadian population who have been formally flagged as representing a disproportionate risk to public safety because of their frequent and serious offending over the life course, (N = 376), we use multiple-failure survival analysis to examine whether formal social control (probation supervision) and informal social bonds (to employment, family, and other prosocial community supports) are related to intermittency in offending. We also investigate whether social bonds moderate the relationship between probation and intermittency. Findings indicate that probation, employment and romantic relationships reduce the hazard of reoffending. Longer periods of probation were related to a lower hazard of reoffending for those who have been employed for longer than six months. While probation length has an effect on intermittency, the mere presence of social bonds reduces the hazard of reconviction. Given the importance of prosocial relationships outside of formal systems of control, we argue for policies that are non-punitive, particularly since lengthy periods of probation can also extend system involvement, which can stall the desistance process.